Manejo genético para a conservação ex situ do Mutum-do-Sudeste, Crax blumenbachii (aves, cracidae) - Costa, Mariellen Cristine (2015)
Captive populations of endangered species are often small, isolated, and founded by a limited number of individuals, which makes them more susceptible to genetic drift and inbreeding effects. Thus, the preservation of the maximum genetic variability is a major concern of captive breeding programs, and understanding the levels of population structuring and genetic variability is important for developing management strategies of captive populations. The Red-billed Curassow (Crax blumenbachii) is endemic to the Brazilian lowland Atlantic Forests and is considered extinct in most of its original distribution. A captive breeding program was initiated during the 70s with the independent foundation of two breeding stocks, that posteriorly supplied animals to other aviaries. With the success of the captive propagation, a reintroduction program has started in 1991, and more than 226 animals have been released into the wild so far. However, animals descending from only one aviary have been used, and the capability of other lineages to increase genetic variability in these, and future released populations, has never been investigated. Then, we analyzed the genetic structure and diversity of the founders and two further important breeding facilities reproducing this species, using 8 microsatellite loci. Bayesian clustering analysis revealed two distinct groups that were in Hardy–Weinberg equilibrium and did not present significant evidences of inbreeding. The existence of two distinct lineages in captivity has implications for breeding and reintroduction programs. We recommend populations to be managed as independent units, but admixted individuals should be produced as a manner to increase reintroduction success.